Bacterial-Polyhydroxybutyrate for Biocompatible Microbial Electrodes - de Moura Torquato, Lilian Danielle [UNESP]; Lacalamita, Dario; Matteucci, Rosa Maria; Franco, Jefferson Honorio; Labarile, Rossella; Perrotta, Alberto; Trotta, Massimo; Farinola, Gianluca Maria; Boldrin Zanoni, Maria Valnice [UNESP]; Grattieri, Matteo; Stufano, Paolo (The Electrochemical Society, 2024)
Highlights Biobased electrode for microbial electrochemical systems. Bacteria-produced polymer for devices with enhanced colonization. Improved biofilm formation and photocurrent generation.
Keywords: bioelectrochemistry; biopolymers; photoelectrochemistry; photosynthetic bacteria; polyhydroxybutyrate